Regression in the service of bibliotherapy—What can “Captain Underpants” teach us? - Ifrah, Sarit (Frontiers in Psychology, 2024)
Regression in the service of the ego is a unique phenomenon that often occurs within therapeutic settings. In the current study 1 I show how it emerges within child therapy and how bibliotherapy manages to give it presence and thus to process it. The methodology that guided this study was based on a critical reading of psychoanalysis and bibliotherapy theories. In addition, the methodology is based on a therapeutic vignette aimed at demonstrating the qualities of bibliotherapy with children. I claim that bibliotherapy, based as it is primarily on the use of reading and writing processes, offers additional ways of processing and thinking about this phenomenon. The study provides an innovative contribution that is related to the interdisciplinary approach to therapy. There are important links between the two major disciplines examined in this study, psychoanalysis and bibliotherapy. Their intertwining generates interrelations and mutual inspiration. Moreover, this study adds to the theoretical and practical foundation of bibliotherapy and further establishes the understanding regarding the power of reading and writing processes to "relate the soul" within the analytical process.